Acceptance and perceived usefulness of robots to assist with activities of daily living and healthcare tasks. Issue 3 (27th May 2019) - Hall, Amanda K.; Backonja, Uba; Painter, Ian; Cakmak, Maya; Sung, Minjung; Lau, Timothy; Thompson, Hilaire J.; Demiris, George
ABSTRACT: As the number of older adults living with chronic conditions continues to rise, they will require assistance with activities of daily living (ADL) and healthcare tasks to continue living independently in their homes. One proposed solution to assist with the care needs of an aging population and a shrinking healthcare workforce is robotic technology. Using a cross-sectional survey design, we purposively sampled adults (≥18 years old) to assess generational acceptance and perceived usefulness of robots to assist with ADLs, healthcare tasks, and evaluate acceptance of robotic healthcare assistance across different settings. A total of 499 adults (age range [years] 18–98, Mean = 38.7, SD = 22.7) responded to the survey. Significant differences were found among young, middle-aged, and older adults on perceived usefulness of robots for cleaning, escorting them around town, acting as companionship, delivering meals, assessing sadness and calling for help, providing medical advice, taking vital sign assessments, and assisting with personal care ( p < 0.05). The majority of younger adults reported that they would like a robot to provide healthcare assistance in the hospital, compared to middle-aged and older adults ( p < 0.001). Results of this study can guide the design of robots to assist adults of all ages with useful tasks.